2008
DOI: 10.3917/jgem.083.0159
|View full text |Cite
|
Sign up to set email alerts
|

Morbidité et soins médicaux aux personnes nées à l'étranger

Abstract: La population des étrangers résidant en France est très hétérogène, tant sur le plan de l'origine géographique, actuellement environ 45 % d'entre eux viennent d'Europe, 39 % d'Afrique, 16 % du reste du monde, que sur la durée de résidence en France, qui s'étend sur des dizaines d'années et la structure de l'immigration selon l'origine géographique a varié au cours des décennies. Par ailleurs, les étrangers sont plus présents dans certaines professions (Cf. annexe 1). Les résultats présentés ici doivent être in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…On the contrary, analysis of the Enquête Trajectoires et Origines did lead to the conclusion of a definite health disadvantage, with however better health among the newly arrived male migrants (Cognet, Hamel, and Moisy, 2012;Hamel and Moisy, 2012;Hamel and Moisy, 2015). In-depth analyses by health economists of the Enquête Décennale Santé and of the Enquête Santé et Protection Sociale either provided no salient difference after adjustment for socio-economic confounders (Mizrahi and Mizrahi, 2008), or provided heterogeneous findings, with no significant difference remaining after adjustment for socio-economic conditions, dietary habits and tobacco and alcohol consumption (Berchet and Jusot, 2009, Berchet and Jusot, 2010. In a cross-national study of populations aged 50 years in 11 European countries, migrants in France generally had worse health than the localborn (Solé-Auro and Crimmins, 2008).…”
Section: Global Indicators Of Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, analysis of the Enquête Trajectoires et Origines did lead to the conclusion of a definite health disadvantage, with however better health among the newly arrived male migrants (Cognet, Hamel, and Moisy, 2012;Hamel and Moisy, 2012;Hamel and Moisy, 2015). In-depth analyses by health economists of the Enquête Décennale Santé and of the Enquête Santé et Protection Sociale either provided no salient difference after adjustment for socio-economic confounders (Mizrahi and Mizrahi, 2008), or provided heterogeneous findings, with no significant difference remaining after adjustment for socio-economic conditions, dietary habits and tobacco and alcohol consumption (Berchet and Jusot, 2009, Berchet and Jusot, 2010. In a cross-national study of populations aged 50 years in 11 European countries, migrants in France generally had worse health than the localborn (Solé-Auro and Crimmins, 2008).…”
Section: Global Indicators Of Healthmentioning
confidence: 99%
“…One study suggested similar utilization of general practitioner care and lower utilization of specialist care among migrants than among native-born (Attias-Donfut and Tessier, 2005), while another one provided evidence for lower utilization of general practitioner care and higher utilization of specialist and hospital care (Mizrahi and Mizrahi, 2008). For equivalent health needs, a more recent study demonstrated that migrants had lower demand for both general practitioner and specialist care (Berchet, 2013).…”
Section: Health-related Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Dans le champ de l'accès aux soins, un constat récurrent est que les immigrés et les étrangers ont une consommation médicale moindre que celle des non-immigrés et des Français (Insee, 2005 ;Mizrahi et al, 2000). Immigrés et étrangers ont en outre un taux plus faible de couverture maladie de base (Mizrahi et al, 2008), ce qui augure de leurs difficultés supérieures pour accéder aux soins. Ce différentiel est plus élevé encore pour la couverture complémentaire (Insee, 2005 ;Marical et al, 2007), dont l'importance pour l'accès aux soins a crû au cours des dernières décennies, à mesure que diminuait le panier de soins pris en charge par la couverture de base.…”
Section: La Recherche Française Et Les Inégalités Selon L'origine Danunclassified
“…Ce différentiel est plus élevé encore pour la couverture complémentaire (Insee, 2005 ;Marical et al, 2007), dont l'importance pour l'accès aux soins a crû au cours des dernières décennies, à mesure que diminuait le panier de soins pris en charge par la couverture de base. Il se traduit par une moindre consommation des étrangers et des immigrés pour les soins particulièrement chers et mal couverts par la couverture de base, comme les soins dentaires (Insee, 2005 ;Mizrahi et al, 2008).…”
Section: La Recherche Française Et Les Inégalités Selon L'origine Danunclassified